Nitrogen Dynamics Variation in Overlying Water of Jinshan Lake, China - Xiaohong Zhou; Mingyuan Wang; Longmei Liu; Zhigang Chen; Yimin Li; Jinping Zhang (Journal of Chemistry)
Jinshan Lake is a famous urban landscape lake with approximately 8.8 km2 water area, which is located on the north of Zhenjiang, of Jiangsu Province, China. Eighteen sampled sites were selected and overlying water was sampled from 2013 to 2014 to study the seasonal and spatial variation of nitrogen in overlying water of Jinshan Lake. Results showed that physicochemical characteristics of temperature, pH, and DO showed high seasonal variation, whereas they had no significant spatial differences in the 18 sampling points (P>0.05) in overlying water of Jinshan Lake. Nitrogen concentrations showed strong seasonal variation trends. The ranked order of TN was as follows: spring > summer > autumn > winter; the order of NH4+-N was as follows: spring > autumn > summer > winter, whereas NO3--N concentrations revealed an inverse seasonal pattern, with maxima occurring in winter and minimal values occurring in spring. Nitrogen concentrations had dramatic spatial changes in 18 sampling points of Jinshan Lake. Physicochemical parameter difference, domestic wastes pollution, and rainfall runoff source may have led to seasonal and spatial fluctuation variations of nitrogen in overlying water of Jinshan Lake, China.